2017
DOI: 10.3390/medicines4020023
|View full text |Cite
|
Sign up to set email alerts
|

Qigong Exercise May Reduce Serum TNF-α Levels and Improve Sleep in People with Parkinson’s Disease: A Pilot Study

Abstract: Background: Inflammatory cytokine levels are often elevated in people with Parkinson’s disease (PD). People with PD often experience sleep disturbances that significantly impact quality of life. Past studies suggest inflammatory cytokines may be associated with various symptoms of PD. Benefits of Qigong, a mind–body exercise, have been shown in different neurological conditions, but there is still a lack of clinical evidence in the PD population. Methods: Ten people with PD were recruited and randomly assigned… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 48 publications
0
26
0
Order By: Relevance
“…The gentle exercise participants were instructed only in the gentle arm movements and postures without the diaphragmatic breathing, clearing of the mind, or chanting of the six healing sounds. A very detailed description of the movements, postures, and sounds has been published previously [26].…”
Section: Intervention Fidelitymentioning
confidence: 99%
“…The gentle exercise participants were instructed only in the gentle arm movements and postures without the diaphragmatic breathing, clearing of the mind, or chanting of the six healing sounds. A very detailed description of the movements, postures, and sounds has been published previously [26].…”
Section: Intervention Fidelitymentioning
confidence: 99%
“…In our feasibility study in a single-arm design (n = 7), a 6-week Qigong exercise program demonstrated an improvement in sleep quality measured by Parkinson’s Disease Sleep Scale-2 (PDSS-2), in which the results showed sub-scores of PDSS-2 were significantly improved or showed a trend of improvement including motor symptoms at night ( p < 0.05) and disturbed sleep ( p = 0.06) in individuals with PD [17]. Our recent pilot study, a randomized controlled trial (RCT), in individuals with PD showed a significant improvement in sleep quality, including PD symptoms at night ( p < 0.05) and total PDSS-2 score ( p < 0.001), after practicing the Qigong exercise for eight weeks (2-week training + 6-week Qigong exercise) [18].…”
Section: Introductionmentioning
confidence: 99%
“…The deep abdominal breathing may stimulate serotonin pathways by stimulating enterochromaffin cells that release serotonin [19] and interact with pro-inflammatory cytokines that contribute to neuroinflammation in the brain [20]. Our recent pilot study suggested potential benefits of Qigong exercise through changes in inflammation status, in which the results showed a significant decrease in serum level of TNF-α from 13.8 ± 0.6 to 12.3 ± 1.6 ( p < 0.05) that was significantly correlated with changes in sleep quality and serum TNF-α level (R 2 = 0.62) [18]. In various medical conditions, mind-body exercises such as Yoga, Tai Chi, and Qigong improved the immune system [21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several complementary medical therapies with some similarities to Qigong are practiced in hospitals in the west and are paid for by insurance. In recent years, existing systematic reviews have examined the clinical evidence of the beneficial effects of Qigong exercise on different medical conditions, such as tumor and cancer, [ 25 27 ] hypertension, [ 2 , 28 , 29 ] diabetes mellitus, [ 30 – 32 ] obesity, [ 33 , 34 ] chronic heart diseases, [ 35 , 36 ] Parkinson's disease, [ 37 39 ] dementia, [ 40 , 41 ] chronic fatigue syndrome, [ 42 44 ] menopause syndrome, [ 45 , 46 ] insomnia, [ 47 49 ] lower back pain, [ 50 52 ] chronic obstructive pulmonary disease, [ 53 55 ] fibromyalgia, [ 56 58 ] metabolic disease, [ 20 , 59 ] osteoarthritis, [ 60 62 ] mental disease, [ 14 , 19 , 63 , 64 ] and so on.…”
Section: Introductionmentioning
confidence: 99%